"You Will Have a Good Career Here, but Not a Great Career": Male Mentoring and the Women Journalists of the Canadian Press News Cooperative, 1965–2000 - Freeman, Barbara M. (Labour / Le Travail, 2016)
Analyzes various forms of discrimination experienced by women journalists at Canadian Press from the mid-1960s to 2000. A feminist, interdisciplinary approach is used to examine masculine newsroom norms and how they affected women's careers. Problems of mentoring are also explored. The study is based on over 30 oral interviews including with women who worked at different times as journalists and editors at CP.